2014
DOI: 10.1111/cpr.12148
|View full text |Cite
|
Sign up to set email alerts
|

Nimbolide inhibits invasion and migration, and down‐regulates uPAR chemokine gene expression, in two breast cancer cell lines

Abstract: These results clearly proved inhibitory effects of nimbolide on tumour cell invasion and migration by down-regulating proteins critically involved in regulation of cell invasion and metastasis, suggesting a possible therapeutic role of nimbolide for breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 52 publications
4
43
0
Order By: Relevance
“…The downregulation of proinvasive and angiogenic proteins, with up-regulationof their inhibitors by nimbolide that was observed in this study was in line with the anti-invasive and anti-angiogenic potential of neem preparations [70]. In addition, nimbolide reduced mRNA expression of MMP-2, MMP-9, uPA and uPA receptor in breast cancer cells (MCF-7) [30]. …”
Section: Mechanism Of Actionssupporting
confidence: 77%
See 3 more Smart Citations
“…The downregulation of proinvasive and angiogenic proteins, with up-regulationof their inhibitors by nimbolide that was observed in this study was in line with the anti-invasive and anti-angiogenic potential of neem preparations [70]. In addition, nimbolide reduced mRNA expression of MMP-2, MMP-9, uPA and uPA receptor in breast cancer cells (MCF-7) [30]. …”
Section: Mechanism Of Actionssupporting
confidence: 77%
“…Additionally, an in vitro study further indicated that nimbolide was able to combat metastasis and angiogenesis of cancer cells [29]. For instance, nimbolide have been shown to effectively decrease breast cancer cell invasion and migration via the transwell invasion and wound healing assays [30]. …”
Section: Anti-cancer Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nimbolide has been shown to exert multiple therapeutic effects and possesses a cyclic enone capable of reacting with cysteines [10][11][12] . In the context of cancer, nimbolide has been shown to inhibit tumorigenesis and metastasis without causing any toxicity or unwanted side effects across a wide range of cancers 10,11,[13][14][15][16][17] . While previous studies suggest that nimbolide impairs cancer pathogenicity through modulating signaling pathways and transcription factors linked to survival, growth, invasion, angiogenesis, inflammation, and oxidative stress the direct targets of nimbolide still remain poorly characterized 10,15,[18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%